Mutual coupling between aperture antennas covered with a dielectric slab - Yap, Alvin Ting Yew. (2009)
Mutual coupling is an adverse effect faced by most antenna systems today, which causes signal degradation. Multiple methods of correcting it have been documented and these can be broadly categorized into namely, Compensation via post-measurement computation, Modifications to existing antenna structures and Structures added to existing antenna structures.